2015
DOI: 10.1016/j.jmb.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Intramolecular and Intermolecular Interactions in Functional Regulation of the Hsp70 J-protein Co-Chaperone Sis1

Abstract: Unlike other Hsp70 molecular chaperones, those of the eukaryotic cytosol have four residues, EEVD, at their C-termini. EEVD(Hsp70) binds adaptor proteins of the Hsp90 chaperone system and mitochondrial membrane preprotein receptors, thereby facilitating processing of Hsp70-bound clients through protein folding and translocation pathways. Among J-protein co-chaperones functioning in these pathways Sis1 is unique, as it also binds the EEVD(Hsp70) motif. However, little is known about the role of the Sis1:EEVD(Hs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(98 citation statements)
references
References 42 publications
15
83
0
Order By: Relevance
“…The Hsp40 used in our assays is encoded by gene DNAJB1. The cooperation of this Hsp40 variant with Hsp70 in refolding assays was reported to be dependent on the presence of the EEVD motif (32,75,76). The association between Hsp40s and the C-terminal structures of Hsp70 seems to represent a more general phenom- FIG.…”
Section: Discussionmentioning
confidence: 97%
“…The Hsp40 used in our assays is encoded by gene DNAJB1. The cooperation of this Hsp40 variant with Hsp70 in refolding assays was reported to be dependent on the presence of the EEVD motif (32,75,76). The association between Hsp40s and the C-terminal structures of Hsp70 seems to represent a more general phenom- FIG.…”
Section: Discussionmentioning
confidence: 97%
“…1B). In addition, alteration of either E50 or R73 to alanine overcame the dependence of Sis1 on EEVD(Hsp70) [11]. Sequence comparison revealed that the charge of these residues is conserved in Sis1 orthologs across species (Fig.…”
Section: Class B J-protein Dependence On Eevd(hsp70) Interactionmentioning
confidence: 99%
“…The templates for Hsp70A1A (Hsp72), DnaJB1, DnaJA2 and Apg2 constructs were obtained from Addgene (Cambridge, MA) cloned into pMAL-His-TEV [17] and expressed in Rosetta 2 (DE3) pLys E. coli cells. DnaJB1, DnaJA2 and Apg2 were purified in a manner similar to that described for Ydj1/Sis1 [11], using Ni chromatography and subsequent removal of MBP-His tag with TEV protease. Hsp72 was purified in a similar manner with an additional ATP agarose chromatography step after TEV cleavage.…”
Section: Protein Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The β-barrel domain specifically interacts with this tetrapeptide. Cytosolic systems of both yeast and humans require this interaction for robust in vitro protein refolding activity [39, 40]. However, this activity of an Hsp70 lacking its EEVD is restored if an intramolecular salt bridge between the J-domain and the adjacent glycine-rich region of its J-protein partner is disrupted, suggesting that intramolecular interactions regulate activity.…”
Section: Chaperone Contacts That Make the System Workmentioning
confidence: 99%